Achieving brand engagement and brand equity through co-creation process - Pereira, T.; Loureiro, S. M. C.; Sarmento, E. M. (Journal of Creative Communications, 2022)
he current study investigates real-time marketing as one strategy for businesses to take advantage of this social and technologic ecosystem. The challenge of a more social and connected consumer is that they engage on online conversations, trends and things. The goal is to analyse the relationship among co-creation, user-generated content (UGC), brand equity and brand engagement. The proposed model revealed a good fit and proved the antecedent role of co-creation on UGC that, in turn, positively influence brand equity and engagement. This study proves that real-time marketing leads to situations of increased UGC—complementing previous findings—and it addresses the gap in the literature proving that real-time marketing leads to situations of increased brand equity and brand engagement.